1980
DOI: 10.1126/science.6251550
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antidepressant Treatment Decreases Spiroperidol-Labeled Serotonin Receptor Binding

Abstract: Antidepressants compete at several neurotransmitter receptor binding site, but drug affinities do not correlate with clinical efficacy. Long-term, but not short-term, antidepressant treatment decreases the numbers of both serotonin and beta-adrenergic receptors. The decrease in the number of receptor sites is most marked for [3H]spiroperidol-labeled serotonin receptors and is characteristic for antidepressants of several classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
210
2
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 822 publications
(228 citation statements)
references
References 17 publications
15
210
2
1
Order By: Relevance
“…First and foremost, a number of placebo controlled trials have found that addition of drugs, which share a common pharmacological action of 5-HT 2 receptor blockade (eg, mianserin, mirtazapine and olanzapine), appear to enhance the antidepressant efficacy of SSRIs (Marek et al, 2003). Second, downregulation of 5-HT 2A receptors is a common and reasonably specific characteristic for known antidepressant drugs (Peroutka and Snyder, 1980), although some controversy exists regarding the effects of SSRIs. Third, a trend exists for upregulation of 5-HT 2A receptor binding in discrete prefrontal cortical regions of suicide victims from postmortem studies (Pandey et al, 2002;Stockmeier et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, a number of placebo controlled trials have found that addition of drugs, which share a common pharmacological action of 5-HT 2 receptor blockade (eg, mianserin, mirtazapine and olanzapine), appear to enhance the antidepressant efficacy of SSRIs (Marek et al, 2003). Second, downregulation of 5-HT 2A receptors is a common and reasonably specific characteristic for known antidepressant drugs (Peroutka and Snyder, 1980), although some controversy exists regarding the effects of SSRIs. Third, a trend exists for upregulation of 5-HT 2A receptor binding in discrete prefrontal cortical regions of suicide victims from postmortem studies (Pandey et al, 2002;Stockmeier et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Currently in focus is the concept of Sulser et al (1978) which, like many of its predecessors, proposes an association between central noradrenergic activity and the depressed state: specifically, the mechanism underlying successful antidepressant therapy is desensitization of the central beta-adrenergic receptor-coupled adenylate cyclase system. Evidence that 5HT receptors are also down-regulated by TCA (Peroutka and Snyder, 1980;Sugrue, 1981) and that serotonergic innervation seems to play a permissive role in beta-adrenergic receptor desensitization (Brunello et al, 1982) supports the idea of an indoleamine-catecholamine link (Prange et al, 1974) and has resulted in further modification of this concept (Sulser, 1984a(Sulser, , 1984b.…”
mentioning
confidence: 88%
“…1B, Tables 1, 2, and 3). The paradoxical down-regulation of 5-HT 2A receptors was first described in in vivo studies of rats chronically treated with antidepressants by Bergstrom and Kellar in 1979 [4] and Peroutka and Snyder in 1980 [76]. Bergstrom and Kellar [4] demonstrated that chronic treatment with the antidepressant desipramine caused a reduction in serotonin binding sites in the cerebral cortex.…”
Section: Paradoxical Down-regulation Of 5-ht 2a By Antagonistsmentioning
confidence: 99%
“…Bergstrom and Kellar [4] demonstrated that chronic treatment with the antidepressant desipramine caused a reduction in serotonin binding sites in the cerebral cortex. In more complete studies using a high affinity 5-HT 2A radio-labeled ligand, spiroperidol, Peroutka and Snyder [76], described statistically significant down-regulation of 5-HT 2A receptors in the frontal cortex of rats chronically treated with the tricyclic antidepressants amitryptiline, desipramine, and imipramine (Tables 1 and 2).…”
Section: Paradoxical Down-regulation Of 5-ht 2a By Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation